2018
DOI: 10.1111/jphp.12900
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 inhibits autophagy through regulation of Rho/ROCK and PI3K/mTOR pathways in a pressure-overload heart failure rat model

Abstract: The results indicated that Grb1 can exert anti-HF function by inhibiting cardiomyocyte autophagy of rats through regulation of Rho/ROCK and PI3K/mTOR pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Ginsenoside Rb1, a saponin extracted from Panax ginseng, could also increase autophagy and reduce apoptosis through inhibiting Rho/ROCK pathway and activating Akt/mTOR pathway. 184 T A B L E 1 Autophagy regulating natural compounds in cardiac diseases Resveratrol and polydatin are both natural monocrystalline compounds extracted from Polygonum cuspidatum.…”
Section: Natural Products In Preventing MImentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside Rb1, a saponin extracted from Panax ginseng, could also increase autophagy and reduce apoptosis through inhibiting Rho/ROCK pathway and activating Akt/mTOR pathway. 184 T A B L E 1 Autophagy regulating natural compounds in cardiac diseases Resveratrol and polydatin are both natural monocrystalline compounds extracted from Polygonum cuspidatum.…”
Section: Natural Products In Preventing MImentioning
confidence: 99%
“…Zhang et al 178 demonstrated that berberine attenuates adverse left ventricular remodeling and cardiac dysfunction after acute MI and it enhances autophagy initiation, particularly at a lower dosage in rats. Ginsenoside Rb1, a saponin extracted from Panax ginseng , could also increase autophagy and reduce apoptosis through inhibiting Rho/ROCK pathway and activating Akt/mTOR pathway 184 …”
Section: Natural Products That Modulate Autophagy In Cardiac Diseasesmentioning
confidence: 99%
“…32 It was reported that ginsenoside Rb1 inhibited autophagy through regulation of Rho/ROCK and PI3K/mTOR pathways in a pressure-overload heart failure rat model. 36 On the contrary, ginsenoside Rg1 could promote autophagy and thus inhibit apoptosis via AMPK/mTOR signaling in serum deprivation macrophages. 52,55 Rg1 and Rb1 are 2 major compounds in ginsengs, but the ratios of Rg1/Rb1 are different among the 3 ginsengs.…”
Section: Action On Cardiovascular and Cerebral-vascular Diseasesmentioning
confidence: 99%
“…54 Moreover, PPT-type saponins should be autophagy inhibitors, for example, Rb1. 36,37,39 However, the transformed PPT-type ginsenosides, such as Rg3 58 and Rh2, were autophagy promoters. 73 The PPD-type oligoglycosides were autophagy promoters, for example, Rg1 and its transformed ginsenoside, such as Rh4.…”
Section: Structure-activity Relationship Of Ginsenosides From Notoginseng In Autophagymentioning
confidence: 99%
“…Regarding its effect on AS, previous studies have already shown that the most abundant active component of ginseng, Ginsenoside Rb1 (Rb1), reduces lipid accumulation in macrophage foam cells and enhances atherosclerotic plaque stability [22]. In addition, the close interaction between Rb1 and the PI3K/Akt pathway also supports the anti-atherogenic function of the compound [23]. Therefore, it was reasonable to assess the effect of Rb1 on dysfunctional ECs as well as on the activity of GPER in those cells, which would not only explain the mechanism driving the anti-atherogenic function of Rb1, but also provide a novel treatment agent against EC dysfunction.…”
Section: Introductionmentioning
confidence: 99%